Analisis Pengaruh E-Ticketing Terhadap Pendapatan Hotel Grand Darusalam Syariah - Mira Yuniar Siregar; Dahrani Dahrani (Yayasan Rahmat Islamiyah, 2022)
The purpose of this study was to determine the effect of E-Ticketing on the revenue of Grand Darussalam Syariah Hotel. This type of research uses quantitative research. The population in this study were guests who booked rooms from the last 5 months, namely from December 2021 to June 2022, namely 1,500 and the sample used was 50 people using accidental sampling and purposive sampling. Data collection techniques used in this study are questionnaires, interviews, and documentation. The analytical model used in this study is a regression analysis model, with the F-test and T-test methods. The results of the T-test of this study indicate that the quality of the system has a significant effect on hotel income. Meanwhile, information quality, service quality, and user quality have no significant effect on income. While the results of the F test Simultaneously system quality, information quality, service quality, user quality simultaneously affect hotel revenue.